Associating Interference with Strategy Instruction: An Investigation into the Learning of the Present Continuous - Jason Miin-Hwa Lim (2006)
Analysing errors committed by second language learners in the acquisition of English tenses, particularly the present continuous, can offer great insights into learners’ difficulties in acquiring target language rules. Focusing on a set of eight rules governing the use of the present continuous, one of the verb forms frequently employed in daily conversations, the researcher employed elicitation procedures aimed at discovering difficulties encountered by learners in second language acquisition. With reference to the errors analysed, the researcher claims that the learners’ first language is not the only linguistic factor affecting the acquisition of English tenses. The learners’ failure to grasp the significance of auxiliary verbs used in combination with the inflectional suffixes of the main verbs, in particular, has been identified as a factor causing learning difficulties. While the subjects’ inability to relate some verb forms to temporal and frequency adverbials may be ascribed to intralingual interference, which is associated with developmental sequence and general learning strategies, it is interesting to note that interference causing a large portion of the errors may be both intralingual and interlingual in nature. On the basis of the data elicited, it is recommended that both finite and non-finite verbs should be explained in relation one another in the syntactic, semantic and morphological aspects. Cognitive and memory-related learning strategies are also recommended to enhance the learning of the present continuous in relation to other verb forms and their associated semantic functions.